2019
DOI: 10.1083/jcb.201812098
|View full text |Cite
|
Sign up to set email alerts
|

SNX27–retromer assembly recycles MT1-MMP to invadopodia and promotes breast cancer metastasis

Abstract: A variety of metastatic cancer cells use actin-rich membrane protrusions, known as invadopodia, for efficient ECM degradation, which involves trafficking of proteases from intracellular compartments to these structures. Here, we demonstrate that in the metastatic breast cancer cell line MDA-MB-231, retromer regulates the matrix invasion activity by recycling matrix metalloprotease, MT1-MMP. We further found that MT2-MMP, another abundantly expressed metalloprotease, is also invadopodia associated. MT1- and MT2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 147 publications
(267 reference statements)
1
41
0
1
Order By: Relevance
“…Thus, it will be of great interest to investigate if these molecules also play a role in the polarization and signaling triggered in the APC. Furthermore, some findings on SNX27 and DAG dynamics during IS formation could be extrapolated to other models of polarized trafficking such as invadopodia formation or the neuronal synapse, where SNX27 is associated with numerous pathological conditions [131][132][133][134].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it will be of great interest to investigate if these molecules also play a role in the polarization and signaling triggered in the APC. Furthermore, some findings on SNX27 and DAG dynamics during IS formation could be extrapolated to other models of polarized trafficking such as invadopodia formation or the neuronal synapse, where SNX27 is associated with numerous pathological conditions [131][132][133][134].…”
Section: Discussionmentioning
confidence: 99%
“…The importance of this complex is underscored by the fact that SNX27 deficiency or mutation is associated with synaptic dysfunction and a variety of neurological diseases such as Alzheimer's disease or Down syndrome [131,132]. Additionally, recent studies suggested that SNX27-retromer-mediated trafficking favors breast cancer metastasis [133,134]. Therefore, further research on SNX27 will shed light on immune and neuronal function and dysfunction, as well as increase the understanding of tumor invasiveness.…”
Section: Int J Mol Sci 2020 21 X For Peer Review 7 Of 17mentioning
confidence: 99%
“…endosomal signal transduction before being trafficked to the cell surface (4). Interestingly, several latest research reports have indicated that SNX27 may contribute to cancer development via recycling cancer-associated proteins (5,6).…”
Section: Sorting Nexin 27 As a Potential Target In G Protein-coupled mentioning
confidence: 99%
“…SNX27 knockdown dramatically decreased cell motility owing to increased expression of E-cadherin and β-catenin, which contributes to adhesion formation and mesenchymal-epithelial transition. Studies have further shown that SNX27 regulates matrix invasion by cancer cells by recycling matrix metalloprotease depending on its direct interaction (6,60). Additionally, SNX27 is involved in regulating energy substance uptake in cancer cells via recycling energy transport receptors.…”
Section: Snx27 and Cancermentioning
confidence: 99%
See 1 more Smart Citation